THE ALGERIAN UNIVERSITY: TRAJECTORY AND REALITY - Sofiane Mimoune, (International Journal of Innovative Technologies in Social Science, 2025)
This paper seeks to explain the path taken by the Algerian university, setting out its central features since its founding during the colonial period, and then working to trace its line after independence when Algeria inherited the French colonial university. There was what was known as university reform in 1971. An attempt by those responsible for higher education, on the one hand, to get rid of the legacy of colonialism, especially from a cultural point of view, and, on the other hand, to keep up with the progress and the requirements of modern technology. Some goals of the reform are Arabization, the connection of the university with development, regard to people, and technology, as well as the democratization and Algerianization of education. Notwithstanding all attempts at reform, the reality of the university has not yet achieved what the reform engineers aimed for. We can note this in particular in the various negative phenomena that the Algerian university suffers from in its various aspects, such as : 1. The demographic fact: the large number of students seemed to impede the institution of the university, although the real impediment lies in coping with these numbers, which indicates a failure to deal with this situation. 2. The pedagogical fact: It indicates some forms of pedagogical design that do not take into account the specificities of society and the persistence of some bad practices in the pedagogical field by professors and students. It also indicates some other phenomena, such as the introduction of ready-made curricula and the interest in the formal aspects at the expense of the essential and the useful aspects. 3. Cultural fact: which reflects the ideological conflicts within the Algerian university. This had repercussions on the scientific dimension and on the objectivity of treating scientific topics. 4: The union fact: It reveals how student organizations work by using these bodies to serve personal interests.